Unidade de ensino potencialmente significativa (UEPS) para o ensino de citologia - Ludtke, Karine Soares (2023)
Difficulties in the teaching-learning process of High School Biology were detected after a few years of experience in teaching practice, especially in the subject of knowledge of Cytology, also called Cellular Biology. Students consider it very complex, abstract and have difficulty associating it with their daily lives, resulting in less interaction with the teacher during classes. The use of didactic sequences (DS) assists in teaching action, as it allows the teacher to insert into their planning, in a systematic and reflected way, the strategies and didactic resources that they identify as relevant to treat objects of knowledge in order to facilitate learning. . The Potentially Meaningful Teaching Units (UEPS) proposed by Moreira, are a type of SD that has its steps built based on Ausubel's Meaningful Learning Theory (TAS). Thus, in this work, as an educational product, a UEPS was developed and applied for teaching Cytology, in the High School Biology curricular component. The development of the proposal sought to answer the following question: "What are the potentialities that a UEPS based on the use of different strategies and teaching resources can promote for learning Cytology?" The UEPS was created using various teaching strategies and resources, such as: reading scientific text, laboratory practices, use of concrete material such as edible models, as well as digital technologies such as the augmented reality application "Biologia UTPL RA", production of short videos by part of students and gamification using Kahoot©. This UEPS was applied to a 1st year high school class at the 7 de Setembro Full-Time State High School, located in the municipality of Espigão do Oeste - RO. The research was qualitative in nature and constituted as action research; the collection instruments used were the teacher's logbook, participant profile and evaluative questionnaires (pre- and post-test and Kahoot©). The profile survey of participants showed that 56% like the Biology curricular component and 96% like technologies; the majority (92%) do not usually read subjects related to Science, 56% study by reading teaching material and 32% discussing the topics with their colleagues. The comparative analysis between the results of the pre- and post-test indicated that there was an increase in the rate of correct answers on the part of the students, but the majority of the more specific, less inclusive concepts did not reach 50% of correct answers. The results obtained with gamification, carried out after the post-test and also involving the Cytology concepts studied, led to better results in terms of correct answers, 66.5% as an overall average, and the majority of students achieved satisfactory performance. Thus, the UEPS, based on the diversification of teaching strategies and resources, brought a more dynamic vision to the object of Cytology knowledge, promoted greater interaction and participation of students in classes, and made it possible to highlight the occurrence of signs of learning on the part of students. UEPS, an educational product, is free and freely accessible and is available for download on the EduCapes portal at http://educapes.capes.gov.br/handle/capes/743283.